2021
DOI: 10.1002/jmv.27526
|View full text |Cite
|
Sign up to set email alerts
|

Omicron and Delta variant of SARS‐CoV‐2: A comparative computational study of spike protein

Abstract: Emerging severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) variants, especially those of concern, may have an impact on the virus's transmissibility and pathogenicity, as well as diagnostic equipment performance and vaccine effectiveness. Even though the SARS-CoV-2 Delta variant (B.1.617.2) emerged during India's second wave of infections, Delta variants have grown dominant internationally and are still evolving. On November 26, 2021, World Health Organization identified the variant B.1.1.529 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
460
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 501 publications
(474 citation statements)
references
References 34 publications
8
460
3
3
Order By: Relevance
“…At first glance, the present results may not seem to be consistent with recent studies on the Omicron variant, which suggested an increase in virulence [10][11][12][13][14][15][16][17][18][19][20][21][22]. These studies evaluated whether the pre-existing immunological memory induced by previous vaccines or infection continues to be effective against the Omicron variant, but in the present study, the antigenicity of the Omicron variant itself was evaluated.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…At first glance, the present results may not seem to be consistent with recent studies on the Omicron variant, which suggested an increase in virulence [10][11][12][13][14][15][16][17][18][19][20][21][22]. These studies evaluated whether the pre-existing immunological memory induced by previous vaccines or infection continues to be effective against the Omicron variant, but in the present study, the antigenicity of the Omicron variant itself was evaluated.…”
Section: Discussioncontrasting
confidence: 84%
“…Therefore, the Omicron variant may not cause severe symptoms. However, due to its high infectivity and transmissibility, as suggested by other studies [10][11][12][13][14][15][16][17][18][19][20][21][22], the Omicron variant should still be regarded with alarm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of writing, we are witnessing the rapid replacement of the delta variant by a new variant, Omicron, which has a higher transmission capacity than all the previous variants, but also has substantial antigenic changes. Omicron has been first characterised in South Africa (B.1.1.529 lineage,"Weekly epidemiological update on COVID-19 -21 December 2021," n.d.) and exhibits the highest number of genomic mutations reported so far, especially in the spike glycoprotein where over 30 substitutions are present (Kumar et al, 2021). Such changes in the most important antigen of the virus, against which the neutralising humoral response is built, have the potential to significantly reduce the efficacy of both vaccines and therapeutic antibodies currently in clinical use (Malani et al, 2021;Taylor et al, 2021), as most of them were designed from the spike protein of the original SARS-CoV-2 strain (Baum et al, 2020;Cathcart et al, 2021;Jones et al, 2021;Kim et al, 2021).…”
Section: Short Communicationmentioning
confidence: 99%